(untitled) (Biological Sciences - PJSIR, 1998)
A rapid and sensitive method for the separation and determination of titanium and iron in thiocyanate system has been developed. The extractability of Ti(Il) by high molecular weight amine (HMWA) in organic solvent (CHCI,) and its separation from Fc(H1) was examined. The yellow coloured complex of Ti(lI)-SCN is quantitatively extracted into the organic phase containing tribenzylamine (TBA)-a high molecular weight amine, whereas the blood red coloured complex of Fe(III)-SCN formed under the same conditions gets separated in the aqueous phase. On the basis of the selective extractability, a method has been developed for the separation as well as simultaneous determi- nation of Ti(1I) and Fe(III) in presence of many other elements. The molar extinction coefficients were found to be 1.9 x 105 I mol" ern" and 1.11xIOS I mol’ I em:’ respectively for Ti(JI) and Fe(III). The extractability of the complex of Ti(Il)-SCN by HMWA suggests that the colourcd species is anionic in nature. The method developed was success- fully applied to the determination of titanium in Cherat volcanic ash.